Comparative assessment of the Tessier and BCR sequential extraction methods for the evaluation of vanadium speciation in the soil - Шуранкова Olga; Nikitin, Aleksander; Cheshyk, Ihar; Kalinichenko, Sergey (Journal of the Belarusian State University. Ecology, 2023)
Tessier and BCR methods for fractionated extraction of forms of vanadium from soil were tested. The methods designed to predict pollutants bioavailability and behavior in the soil. Data on the vanadium speciation by forms with different mobility and biological availability in soddy-podzolic soils are presented. Comparison of two sequential extraction schemes regarding vanadium shows the relative comparability of approaches to assessing the distribution of the element according to the forms in the soil. Significant differences in the use of these methods were noted in the percentage of the vanadium associated with iron and manganese oxides. The proportion of this form according the BCR method is more than 3 times higher than the percentage of a similar form according the Tessier method. Vanadium can be attributed to the group of inaccessible heavy metals, it is hardly available to the root uptake of plants. Vanadium, as a rule, is concentrated in fractions that are not extractable and fixed on soil minerals. The total percentage in the water dissolved and ion-exchange forms is below 2 %.